Analysis of Factors Influencing Mental Health in Adolescents: Literature Review - Ramdani, Ubaidillah; Azari, Abdul Aziz (Universitas Muhammadiyah Semarang, 2024)
Adolescence is a period of rapid growth and development, both physically, psychologically, and intellectually. Adolescents have great curiosity, like adventure and challenges, and dare to make decisions without careful consideration. If the decision is not correct, it can risk causing various physical and psychosocial health problems. This literature review aims to determine the factors influencing adolescent mental health. The data for this study were taken from four relevant databases, PubMed, Science Direct, EBSCO, and Google Scholar, using the PIOS (Participant, Intervention, Outcomes, and Study Design) method and MeSH terms on the search engine. The keywords